Izin Praktek Keperawatan Mandiri Sebagai Pelaksana Fungsi Perawat Dalam Upaya Pelayanan Kesehatan Masyarakat Dihubungkan Dengan UU Kesehatan No. 36 Tahun 2009 - Aceng Ali Awaludin (Jurnal Medika Cendikia, 2016)
delegation of doctors to nurses chronically. As a result, could no separated region (gray area) that should be done by nurses and oppositely. This is one of the triggers of rejection or objection among doctors and nurses therein associated with the Act of Independent Nursing Practice (PKM). Therefore, the nursing paradigm must change that nursing is a professional service, not only to help the tasks of doctor, but to be a part of efforts to achieve the goals of medical care services in the form of license or independent nursing practice as an effort to achieve the goal of nursing care. This research was conducted in order to determine the state of the nurses practice independently as well as a result of such practices, as well as to determine the boundaries of independent nurse practices in line with the practice of the doctor and not detrimental to the health of the other health profession The research uses a qualitative method through inductive-descriptive approach to explain the phenomena occured, the relationship and influence between or against ones to the other phenomenon. The data analysis techniques used are credibility, transferability, dependability, and confirmability to obtain more objective data with a high degree of validity. The research concluded, that the regulation of Independent Nursing Practice in Public Health Care Facilities or hospital, especially in Garut District, has implemented properly, including the owner of licensing SIP, SIK, and SIPP, and Professional Ethics Code so implementing the SOP as it should, and are willing to improve their professional capabilities and the quality of nursing in more conditions and situations. The nurses have the authority to perform nursing actions as complementary agents to replace the absence of a doctor or other medical personnel in certain emergency conditions, and have been able to implement the aspects of nursing management through the planning of health programs in their working area, as well as carry out nursing actions in accordance with their authority. In addition, supervision of the Independent Nursing Practice authority associated with Act No. 36/2009 about Health showed that nurses have authority independent practice mostly registered and obtained a license and the legality or the rule of law with the management objective according to the field. These are indicators of cooperation between nursing staff with other health professionals agents in order to improve public health status.